Pride in Teachers’ Everyday Work. Conditions and Contexts - Pawłowska, Beata (Qualitative Sociology Review, 2020)
The aim of this article is to elaborate on the reasons behind feeling the emotion of pride within the professional context of actions undertaken by contemporary Polish teachers. The article attempts to answer the question of what role pride plays in teachers’ career building process and their daily work. All considerations focus on the social construction of the meaning of pride, established from teachers’ perspectives. Pride is here referred to as social emotion, in line with an interpretivist approach. The following reflections are based on the data collected due to: 1) multiple observations conducted by the author in the years 2008-2016 in the primary, as well as junior high schools; 2) interviews with teachers, parents, and other school staff. Pride in teachers’ work arises in three main contexts: 1) pride due to prestige, 2) pride due to one’s recognition (appreciation), and 3) pride as a result of diverse interactions, for example, teacher-student. The emotion at hand is, like shame, of a social origin and plays a key role when it comes to interactions, social control, as well as maintaining social order. And yet, most of the researchers would give the lead to emotions such as shame, guilt, or related stigma. Based on the collected data, this article focuses on the emotion of pride in the process of identity building by employees—teachers.